PENGARUH PROMOSI DAN SERVICESCAPE TERHADAP KEPUTUSAN MENGINAP MELALUI CITRA MEREK DI ELROYALE HOTEL BANYUWANGI PADA MASA PANDEMI - Christina Natalia Putri Subroto; Theresia Pradiani; Fathorrahman (Journal of Applied Management and Accounting Science, 2021)
During this Pandemic Covid 19 situation, the competition in the hotel industry becomes more competitive. The niche market especially in this industry become smaller and tighter. Thus, the hotel businesses have to be more aware with all the factors than can affect the customer to do the purchase decision to keep their sustainability and to win the competition. Some of the important factors that can affect the consumer decision are promotion, servicescape and brand image. The study was conducted to find out the influence of promotion and servicescape of stay decisions through of brand image at El Royale Hotel Banyuwangi. This research uses a type of quantitive research with path analysis as the method. The tool that was used by the researcher is IBM SPSS 26. The population of this study is the visitors who stay at El Royale Hotel Banyuwangi, with the number of samples used are 100 based on Slovin Formula and taken by purposive sampling technique.The sampling’s criteria that are used in this research are the guests above 17 years old, and the guest who act as a decision maker. The result of this study is show that (1) partially promotion and servicescape affect the brand image positively and significantly. (2) partially promotion, servicescape and brand image affect the stay decision positively and significantly. (3) Brand image able to mediate the influence of promotion to stay decision. (4) Brand image is not able to mediate the influence of servicescape to stay decision.